2014
DOI: 10.1080/00981389.2014.884037
|View full text |Cite
|
Sign up to set email alerts
|

Hospital to Community Transitions for Adults: Discharge Planners and Community Service Providers’ Perspectives

Abstract: Discharges from the hospital to community-based settings are more difficult for older adults when there is lack of communication, resource sharing, and viable partnerships among service providers in these settings. The researchers captured the perspectives of three different groups of participants from hospitals, independent living centers, and Area Agencies on Aging, which has rarely been done in studies on discharge planning. Findings include identification of barriers in the assessment and referral process … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
95
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(97 citation statements)
references
References 32 publications
2
95
0
Order By: Relevance
“…Challenges facing hospital social workers may contribute to the lack of satisfaction of their services. For example, high caseloads, pressure for speedy discharges, and the use of medical model assessments may limit the ability for hospital social workers to provide adequate referrals and the detailed information desired by clients and caregivers (Chapin et al, 2014; Judd & Sheffield). While hospital social workers may not be able to control high caseloads, demand for speedy discharge, or prioritization of other medical professionals, they may be able to implement person and family-centered assessments in social work (Levack et al, 2011; Shyu et al, 2008).…”
Section: Discussion and Applications To Social Workmentioning
confidence: 99%
See 1 more Smart Citation
“…Challenges facing hospital social workers may contribute to the lack of satisfaction of their services. For example, high caseloads, pressure for speedy discharges, and the use of medical model assessments may limit the ability for hospital social workers to provide adequate referrals and the detailed information desired by clients and caregivers (Chapin et al, 2014; Judd & Sheffield). While hospital social workers may not be able to control high caseloads, demand for speedy discharge, or prioritization of other medical professionals, they may be able to implement person and family-centered assessments in social work (Levack et al, 2011; Shyu et al, 2008).…”
Section: Discussion and Applications To Social Workmentioning
confidence: 99%
“…A study found that almost half of hospital social workers had caseloads larger than 60 per month (Judd & Sheffied, 2010). Because of pressure to conduct speedy discharges, social workers often felt as though they did not have enough time to conduct adequate assessments (Chapin et al, 2014). Focus groups with 25 hospital social workers found that it was a “common and appropriate form of practice” to only have a single session with a client prior to their discharge.…”
Section: Hospital Social Work Challengesmentioning
confidence: 99%
“…This care transition intervention differed from others, such as Naylor's Care Transitions Model, Coleman's Care Transition Program [3,24] and others which used a liaison or navigator roles to serve a system-spanning function, linking and coordinating care by facilitating the flow of information between care settings [36]. This particular study attempted to replicate the care coordination benefits of these previous studies by dedicating individuals within each organization the accountability for coordinating the development of the transitional care plan , the hand-off and post-discharge follow-up.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, significant interest has developed around the implementation of care transition interventions, as care coordinating mechanisms, to reduce avoidable readmissions and other adverse events in the post-discharge period [3,[21][22][23][24][25][26][27][28].…”
mentioning
confidence: 99%
“…Among the mentioned barriers that impede timely and secure DP are high workloads among RNs [8, 16], variable schedules among healthcare personnel [17, 18], a lack of trained personnel [19, 20], and ineffective communication for timely exchange [21, 22]. Unclear roles [23], unclear routines, and unstructured information [24] also impede the DP, as does a changing healthcare system, which has seen a reduced number of hospital beds and shorter hospital stays [25].…”
Section: Introductionmentioning
confidence: 99%